Audit quality, public media exposure, environmental, social and governance disclosure and investment efficiency - Zhang, Lu (2022)
There are two primary goals for this study. The paper first investigates the connection between ESG transparency and two elements that might affect a company's ESG transparency, audit quality and public media exposure. Second, it assesses how ESG transparency impacts investment efficiency for a company. In order to investigate the connection between these two factors (audit quality and public media exposure) and ESG transparency od company, we utilise ordinary least square (OLS) regressions to analyse data from a pool of publicly traded UK companies between 2017 and 2021. We then apply an econometric model to look at how under- and over-investment are related to ESG disclosure. Companies are more likely to provide complete and transparent ESG data when they are committed to high-quality audits and are subjected to heavy public media attention, the study found. Inefficient investment is correlated with less ESG transparency at the corporate level. Thus, ESG transparency generates valuable supplemental information, which encourages improved resource allocation through enhanced investment efficiency and aids in the reduction of information symmetry between enterprises and stakeholders. This research contributes to the CSR and ESG literature by establishing that audit quality and public media exposure are two main drivers of company’s ESG transparency. Additionally, it is emphasised that enhanced ESG transparency has a significant economic impact on capital investment decisions by increasing investment efficiency at the corporate level.